A Study to Assess the Knowledge Regarding Glasgow Coma Scale among the Staff Nurses of Selected Hospitals to Develop Information Booklet at Bhuj – Kachchh, Gujarat - Puneet Gangawat; Hiral Vekariya; Acharya Disha; Anisha Roy; Asari Dipali; Barot Khushi; Chhabhadiya Monica; Chudasama Nandani; Dabasiya Hastiben; Dave Divya (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
The use of the GCS became widespread in the 1980s when the first edition of the Advanced Trauma and Life Support recommended its use in all trauma patients. The GCS is used to objectively describe the extent of impaired consciousness in all types of acute medical and trauma patients. The scale assesses patients according to three aspects of responsiveness: eye-opening, motor, and verbal responses. The GCS and its total score have since been incorporated into numerous clinical guidelines and scoring systems for victims of trauma or critical illness. Objectives: The objective of the study is to assess the knowledge regarding GCS among the staff nurses of selected hospitals. Findings: Demographic variables of staff nurses are depicted in which 11 (18.33%) had adequate knowledge regarding GCS, 36 (60.00%) had had moderately adequate knowledge and 13 (21.66%) had inadequate knowledge. Conclusion: The study result revealed that the staff nurses were having lack of knowledge regarding GCS and were inadequate knowledge regarding the same these findings of the study were mind-boggling and are suggestive of a need to research to assess the effectiveness of some strategies to improve knowledge of staff nurses regarding GCS. The study shows that the majority of the staff nurses had moderately adequate knowledge and moderately adequate satisfaction regarding the effectiveness of GCS among staff nurses in selected hospitals of Bhuj-Kachchh, Gujarat.